2018
DOI: 10.1002/ange.201807113
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Syngas into Methyl Acetate, Ethanol, and Ethylene by Relay Catalysis via the Intermediate Dimethyl Ether

Abstract: Selective conversion of syngas (CO/H2) into C2+ oxygenates is a highly attractive but challenging target. Herein, we report the direct conversion of syngas into methyl acetate (MA) by relay catalysis. MA can be formed at a lower temperature (ca. 473 K) using Cu‐Zn‐Al oxide/H‐ZSM‐5 and zeolite mordenite (H‐MOR) catalysts separated by quartz wool (denoted as Cu‐Zn‐Al/H‐ZSM‐5|H‐MOR) and also at higher temperatures (603–643 K) without significant deactivation using spinel‐structured ZnAl2O4|H‐MOR. The selectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We will discuss in detail the structural descriptors that dictate the dissolution behavior of zeolite crystals leading to materials with a multi-model pore structure. The feasibility of this approach is exemplified by the treatment of the MOR-type zeolite [19], an essential active component in a number of catalytic reactions, such as carbonylation [20][21][22], conversion of methane into methanol [23], selective conversion of syngas [24], selective catalytic reduction of NOx [25], hydroisomerization [26] and others. Besides the 12-member ring (MR) channel running along the c axis, mordenite contains an 8-MR side pocket that could contribute substantially to its performance [27][28].…”
Section: Introductionmentioning
confidence: 99%
“…We will discuss in detail the structural descriptors that dictate the dissolution behavior of zeolite crystals leading to materials with a multi-model pore structure. The feasibility of this approach is exemplified by the treatment of the MOR-type zeolite [19], an essential active component in a number of catalytic reactions, such as carbonylation [20][21][22], conversion of methane into methanol [23], selective conversion of syngas [24], selective catalytic reduction of NOx [25], hydroisomerization [26] and others. Besides the 12-member ring (MR) channel running along the c axis, mordenite contains an 8-MR side pocket that could contribute substantially to its performance [27][28].…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 hydrogenation to various products is one of the most extensively studied topics. Among all the possible products via this route, the production of dimethyl ether (DME) stands out as a promising way for the utilization of CO 2 . Not only does DME serve as building block for the synthesis of methyl acetate (MA), acetic acid (AA), and even ethanol through carbonylation reactions, it is also a possible substitute for propane in the liquefied petroleum gas (LPG) and clean fuel for diesel engines, ,, which could serve as an option for reducing the petroleum dependency. Therefore, the study of CO 2 hydrogenation to DME has been attracting more and more attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Three likely mechanisms were proposed: (i) sequential hydrogenation mechanism via formyl and methoxy intermediates to methanol, (ii) formate mechanism via formate and methoxy intermediates to methanol, and (iii) side-on hydrogenation mechanism via formaldehyde and methoxy intermediates to methanol . Recently, combinations of metal oxide composites and zeolites have demonstrated great capacities in selectively catalyzing CO or CO 2 hydrogenation to a variety of valuable chemicals. Spinel ZnAl 2 O 4 was used as a component of the catalysts for CO and CO 2 hydrogenations. ,, Saussery and Lavalley studied CO hydrogenation to methanol catalyzed by 15% Cu-ZnAl 2 O 4 at 1.0 MPa of 525 K and proposed that ZnAl 2 O 4 was responsible for the formation of bidentate formate and methoxy intermediates and copper promoted the formate reduction reaction, in which the rate-controlling step was the desorption of methoxide. Liu et al reported that ZnAl 2 O 4 itself could selectively catalyze syngas to dimethyl ether and methanol and proposed that the formate species formed by CO reaction with surface OH was the key intermediate for CO hydrogenation to methanol.…”
mentioning
confidence: 99%